What Fuels Natural Killers? Metabolism and NK Cell Responses - Gardiner, Clair M.; Finlay, David K. (Frontiers in Immunology, 2017)
There is a growing appreciation that cellular metabolism is important in determining the course of lymphocyte responses. Additionally, changes in metabolic processes have been linked to dysfunctional lymphocyte functions in a number of different diseases. While most early studies of metabolic regulation of lymphocyte function focused on T lymphocytes, an understanding of how metabolic pathways impact upon natural killer (NK) cell responses is now starting to emerge. In this review article, we will discuss how cellular metabolism influences lymphocyte function with a particular focus upon NK cells.